Harmonisasi Aturan WTO (World Trade Organization) Dengan Undang-Undang Nomor 3 Tahun 2020 tentang Pertambangan Mineral Dan Batu Bara Dalam Sengketa Ekspor Nikel: Studi Kasus Gugatan Uni Eropa Terhadap Indonesia - Zafierdia Aziza Ismail; Dhesy A Kase (Law Faculty, Nusa Cendana University, 2026)
: Indonesia's ban on nickel ore exports since 2020 has triggered a dispute with the European Union at the WTO, as it was deemed to violate Article XI:1 of the GATT 1994, which prohibits quantitative export restrictions. Indonesia argued that the policy aimed to protect natural resources and promote downstream industrialization for the prosperity of its people, as mandated by Article 33 paragraph (3) of the 1945 Constitution. This dispute highlights the tension between national sovereignty over natural resource management and international obligations within the global trade system. The WTO Panel ruled that Indonesia’s policy was inconsistent with the GATT, sparking debate over the fairness and flexibility of WTO rules for developing countries. This study aims to analyze two main issues: (1) The harmonization of WTO rules with Law No. 3 of 2020 in the context of the EU’s complaint, and (2) The impact of the WTO’s decision on Indonesia’s nickel ore export ban policy. The research method used is normative legal research with a qualitative approach based on literature study. The findings indicate that the WTO’s decision in case DS592, which favored the European Union, could potentially undermine Indonesia’s downstream strategy. However, due to the dysfunction of the Appellate Body following a U.S. blockade, the appeal process has been delayed, allowing Indonesia to maintain its export policy for now. If Indonesia wins the appeal, Law No. 3 of 2020 and Minister of Energy and Mineral Resources Regulation No. 11 of 2019 can remain in force. If it loses, the policy must be adjusted to align with GATT 1994, possibly through a limited quota system, progressive export taxes, or downstreaming incentives. Harmonizing policies is crucial to balance national interests with international obligations and to enhance the effectiveness of industrial downstreaming through selective policies and strict supervision.